PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP HASIL PERKEMBANGAN BELAJAR SISWA PADA MATA PELAJARAN PPKn DI SMPN 1 KUBU BABUSSALAM, ROKAN HILIR - Desliani Desliani; Gimin Gimin; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the importance of professional competence with the results of student learning development. The formulation of the problem in this study is whether there is an influence of the professional competence of Civics teachers on the results of student learning development at SMPN 1 KubuBabussalam. The purpose of this study was to determine the effect of the professional competence of PPKn teachers on the results of student learning development at SMPN 1 KubuBabussalam. This type of research used quantitative research. The population in this study were all students at SMP N 1 KubuBabussalam as many as 314 people with a total sample of 76 students. The technique used in sampling is the Slovin formula. Data collection techniques using a questionnaire / questionnaire, observation and documentation. The data analysis technique that the researcher uses is simple linear regression. Based on the results of the study, it can be concluded that there is a positive influence of teacher professional competence on student learning development outcomes, meaning that every time there is an increase in teacher professional competence, there will also be an increase in student learning development outcomes in a better direction. This is reinforced and supported by a significance smaller than the alpha value, which is 0.007 <0.05, meaning that the professional competence of teachers has a positive and significant effect on the results of student learning development at SMPN 1 KubuBabussalam, RokanHilir, RokanHilir. Furthermore, it can be seen that t count is greater than Fcount is greater than Ftable (7.748>3.96) then Ho is rejected and Ha is accepted, indicating that teacher professional competence has a positive and significant effect on student learning outcomes at SMPN 1 KubuBabussalam, RokanHilir , RokanHilir.Key Word: Influence, Professional Competence, Learning Development Outcomes, PPKn